Analysis of Sales Reports as a Basis for Preparing Financial Reports for Warung Bu Tantri Jember - Deo Fikri Aikal; Diva Candra Rista; Fajar Hardian; Hilmi Abdillah; Putri Maulidia Khotijah; Mohammad Riza Ainulyaqin (Medikun Publisher, 2024)
Financial reports are records of a company's financial information in an accounting period that can be used to describe the company's financial performance. According to financial accounting standards issued by the Indonesian Accountants Association, financial reports function as a tool for analyzing financial performance which can provide information about financial position, performance and cash flow, so that it can be used as a basis for making economic decisions. The puIDRose of this writing is to find out the importance of financial reports and designing simple financial reports for Warung Bu Tantri MSMEs. The research used a descriptive data collection method by conducting interviews and direct observation with the owners of the MSMEs. This research shows that there are obstacles experienced by MSMEs, especially in preparing financial reports, because they are incomplete. Without comprehensive financial reports, the information produced is limited. This can make it difficult for business owners to fully understand the financial condition and performance of their business. Sound business decisions and effective financial planning are difficult without complete and detailed data. So in this BU TANTRI UMKM financial report, you don't use an application, just a simple financial report structure. Meanwhile, a good financial report that truly complies with PSAK must be complete and include all relevant elements